2003
DOI: 10.1126/science.1088892
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the RC-LH1 Core Complex from Rhodopseudomonas palustris

Abstract: The crystal structure at 4.8 angstrom resolution of the reaction center-light harvesting 1 (RC-LH1) core complex from Rhodopseudomonas palustris shows the reaction center surrounded by an oval LH1 complex that consists of 15 pairs of transmembrane helical alpha- and beta-apoproteins and their coordinated bacteriochlorophylls. Complete closure of the RC by the LH1 is prevented by a single transmembrane helix, out of register with the array of inner LH1 alpha-apoproteins. This break, located next to the binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
539
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 625 publications
(563 citation statements)
references
References 27 publications
22
539
0
2
Order By: Relevance
“…palustris exists a lowresolution X-ray structure. 4 Accordingly, the RC is enclosed by an overall elliptically shaped LH1 consisting of 15 αβ-subunits that feature a gap, which is also consistent with data from optical single-molecule experiments. 14,15 Each subunit accommodates two light harvesting BChl a molecules giving rise to an absorption band at 875 nm.…”
Section: ■ Introductionsupporting
confidence: 84%
“…palustris exists a lowresolution X-ray structure. 4 Accordingly, the RC is enclosed by an overall elliptically shaped LH1 consisting of 15 αβ-subunits that feature a gap, which is also consistent with data from optical single-molecule experiments. 14,15 Each subunit accommodates two light harvesting BChl a molecules giving rise to an absorption band at 875 nm.…”
Section: ■ Introductionsupporting
confidence: 84%
“…There are no highresolution data of a dimeric RC-LH1 complex, but a 4.8 Å -resolution structure is available for the monomeric RC-LH1 from Rps. palustris [3]. The RC-LH1 structure shows the RC surrounded by an oval LH1 complex, which consists of 15 pairs of transmembrane helical a and b-apoproteins and their coordinated bacteriochlorophylls.…”
Section: Introductionmentioning
confidence: 99%
“…viridis [2], Rhodopseudomonas (Rps.) palustris [3], Phaeospirillum molischianum [4], Rhodobacter (Rba.) veldkampii [5,6], Rps.…”
Section: Introductionmentioning
confidence: 99%
“…The complex LH1, which surrounds the reaction center (RC), is composed of B880, a bacteriochlorophyll dimer with an absorption maximum at 880 nm. These structures ostensibly exhibit formation as a ring when studied independently, though some studies have suggested that the ring is not closed when the RC is present [21,26]. The LH1 complex is in turn surrounded by a number of LH2 complexes, comprising both B850 rings above and B800 rings below.…”
Section: Light-harvesting Complexesmentioning
confidence: 99%
“…In order to most effectively utilize the sunlight that falls on them, all photosynthetic organisms have a system of antenna complexes surrounding the reaction centers where photosynthesis takes place. The photosystems of purple bacteria, such as Rhodopseudomonas acidophila and Rhodobacter sphaeroides [19], have been most extensively studied [20][21][22] by means of ultrashort pulsed laser spectroscopy [23], X-ray protein crystallography [24], as well as hole-burning and absorption studies [25]. In such systems bacteriochlorophyll is the key light-harvesting pigment.…”
Section: Light-harvesting Complexesmentioning
confidence: 99%